2017
DOI: 10.1177/0284185117695668
|View full text |Cite
|
Sign up to set email alerts
|

Shear-wave ultrasound elastography of the liver in normal-weight and obese children

Abstract: Background The identification and subsequent management of liver diseases in children is challenging due to the lack of non-invasive imaging biomarkers. Ultrasound shear-wave elastography (US-SWE) is an emerging imaging technique which can quantitatively assess liver stiffness and may be useful as a tool in the management of liver disease in overweight and obese children. Purpose To evaluate US-SWE velocities of the liver in normal-weight and obese children, to correlate US-SWE findings with age and body-mass-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 35 publications
4
31
1
Order By: Relevance
“…Studies showed that it has excellent intraobserver and interobserver error, intraclass correlation coeffiients in three different sections of the liver ranged from 0.86 to 0.98, and the 95% confidence interval ranged from 0.71 to 0.99, suggesting the technique is highly reproducible [23,26]. An non-invasive procedure, it is very suitable for detecting therapeutic outcome after operations, such as liver transplantation [33] and can be used for screening and subsequent management of liver diseases, particularly for children [34]. Other advantages of this method include determining therapeutic response, and monitoring age-related changes, including sarcopenia and clinical frailty syndrome.…”
Section: Discussionmentioning
confidence: 95%
“…Studies showed that it has excellent intraobserver and interobserver error, intraclass correlation coeffiients in three different sections of the liver ranged from 0.86 to 0.98, and the 95% confidence interval ranged from 0.71 to 0.99, suggesting the technique is highly reproducible [23,26]. An non-invasive procedure, it is very suitable for detecting therapeutic outcome after operations, such as liver transplantation [33] and can be used for screening and subsequent management of liver diseases, particularly for children [34]. Other advantages of this method include determining therapeutic response, and monitoring age-related changes, including sarcopenia and clinical frailty syndrome.…”
Section: Discussionmentioning
confidence: 95%
“…TE has some limitations in young children; some authors reported technical failure in 17% of children younger than 2 years old, and others reported technical failure in 10% of children of any age . SWE is a noninvasive imaging technique that shows promising reliability and clinical utility for the quantitative assessment of liver tissue stiffness, particularly in children . While numerous studies have been conducted on SWE measurement of healthy adult livers, few studies have evaluated SWE in children, especially in school‐age children.…”
Section: Introductionmentioning
confidence: 99%
“…In the obese group, mean shear wave velocity was statistically higher in children with abnormal echogenic livers than in those with normal-appearing livers (1.53 ± 0.38 vs 1.17 ± 0.27). The difference was not significant in the normal-weight group [50].…”
Section: Factors Influencing Liver Stiffness Independent Of Liver Fibmentioning
confidence: 65%
“…There was no statistical difference between measurements taken at different ages [51,52]. Conversely, in another study pSWE speed was primarily associated with age, BMI, but not with gender [50]. Other important factors are the transducer's frequency and the operator experience [53][54][55][56][57].…”
Section: Comparison Of Results Between Systems In Pediatric Patientsmentioning
confidence: 83%